Distal Femoral Locking Plates and the Posterolateral Corner - Wittstein, Jocelyn Ross; Watson Mayer, Stephanie; Mayer, Braden; Krenzel, Brian; Deshpande, Chetan; Zura, Robert (The Journal of Knee Surgery, 2013)
The purpose of this study was to evaluate the effect of minimally invasive submuscular placement of a distal femoral locking plate on the posterolateral structures of the knee. Eight fresh-frozen cadaveric knees were dissected after application of a lateral distal femoral locking plate through a minimally invasive submuscular approach. The lateral collateral ligament and popliteus tendon were identified and inspected for injury. Distances from the plate to the lateral collateral ligament and popliteus insertions were determined.Neither the lateral collateral ligament nor the popliteus tendon was disrupted by the minimally invasive submuscular application of distal femoral periarticular locking plates. The mean distances to the lateral collateral ligament and popliteus tendon insertions were 2.5 and 6.6 mm, respectively.Distal femoral locking plates can be applied in a minimally invasive manner without disrupting the posterolateral structures of the knee.
Keywords: posterolateral corner; locking plate; knee trauma